The Transcriptomic and Phenotypic Response of the Melanized Yeast Exophiala dermatitidis to Ionizing Particle Exposure - Schultzhaus, Zachary; Chen, Amy; Shuryak, Igor; Wang, Zheng (Frontiers in Microbiology, 2021)
Fungi can tolerate extremely high doses of ionizing radiation compared with most other eukaryotes, a phenomenon encompassing both the recovery from acute exposure and the growth of melanized fungi in chronically contaminated environments such as nuclear disaster sites. This observation has led to the use of fungi in radiobiology studies, with the goal of finding novel resistance mechanisms. However, it is still not entirely clear what underlies this phenomenon, as genetic studies have not pinpointed unique responses to ionizing radiation in the most resistant fungi. Additionally, little work has been done examining how fungi (other than budding yeast) respond to irradiation by ionizing particles (e.g. protons, α-particles), although particle irradiation may cause distinct cellular damage, and is more relevant for human risks. To address this paucity of data, in this study we have characterized the phenotypic and transcriptomic response of the highly radioresistant yeast Exophiala dermatitidis to irradiation by three separate ionizing radiation sources: protons, deuterons, and α-particles. The experiment was performed with both melanized and non-melanized strains of E. dermatitidis, to determine the effect of this pigment on the response. No significant difference in survival was observed between these strains under any condition, suggesting that melanin does not impart protection to acute irradiation to these particles. The transcriptomic response during recovery to particle exposure was similar to that observed after γ-irradiation, with DNA repair and replication genes upregulated, and genes involved in translation and ribosomal biogenesis being heavily repressed, indicating an attenuation of cell growth. However, a comparison of global gene expression showed clear clustering of particle and γ-radiation groups. The response elicited by particle irradiation was, in total, more complex. Compared to the γ-associated response, particle irradiation resulted in greater changes in gene expression, a more diverse set of differentially expressed genes, and a significant induction of gene categories such as autophagy and protein catabolism. Additionally, analysis of individual particle responses resulted in identification of the first unique expression signatures and individual genes for each particle type that could be used as radionuclide discrimination markers.